A method for capturing and GPS tracking breeding White-backed Woodpeckers Dendrocopos leucotos. Issue 2 (2nd April 2020) - Campión, David; Elosegi, Miguel Mari; Cabodevilla, Xabier; Villanúa, Diego
ABSTRACT: Capsule : The use of mist nets placed at more than 9 m high and small GPS tags fitted with a pelvic harness, and equipped to download remotely, allows the capture and tracking of breeding White-backed Woodpeckers Dendrocopos leucotos . Aims : To describe and test a method for capturing, ringing and GPS-marking medium-sized woodpeckers. Methods: Birds were captured using an overlapping mist net system located between two poles with a minimum height of 9.25 m and a maximum of 12.95 m, previously designed for catching bats. Once captured, the birds were ringed and fitted them with a remote download GPS tag, weighing 3.4 g. Results : Twenty individuals (17 adults and 3 juveniles) from 14 territories were captured during the 28 sampling days. All marked breeders continued with chick provisioning and in 12 of the territories were successful in fledging young. We found no significant difference in the number of fledglings between nests where the breeders were captured and tagged with devices (1.71 ± 0.19 se) and nests where the breeders were not captured (1.71 ± 0.29 se). The GPS tags allowed us to obtain a mean of 102.6 (±15.91 se) locations for each bird during a tracking period averaging 57.8 (±10.4 se) days. Despite the steep slope and the high forest canopy in the hábitat, 77.09% of GPS locations were accurate to within 20 m. Conclusion : Our results showed that this method allows us to obtain important information about the habitat use of this species during the breeding period without any apparent effect on reproductive success.